Hormone Resistance and Other Endocrine Paradoxes - Cohen, Margo Panush (Endocrinology and Metabolism, Progress in Research and Clinical Practice, 1987)
This volume is the first in a new series entitled "Endocrinology and Metabolism: Progress in Research and Clinical Practice". It explores a wide range of clinical conditions in terms of the challenge they pose to current concepts in endocrinology. These conditions include pseudohypoparathyroidism, characterized by target organ resistance to parathyroid hormone; vitamin D resistance syndromes associated with calcitriol receptor abnormalities; and androgen sensivity syndromes in which normal testicular androgen synthesis and secretion coexist with phenotypic feminization. The endocrine paradox phenomenon is further elucidated through comprehensive discussions of the pathophysiology and treatment of major disorders in mineral homeostasis due to aldosterone deficiency and pseudodeficiency (with emphasis on hormonal derangements in Bartter's syndrome); euthyroid hyperoxinemia; and clinical and physiologic implications of insulin gene mutations and subsequent defects in insulin biosynthesis.